Pengaruh Pengungkapan Nilai Etika Islam terhadap Kinerja Bank Syariah di Indonesia - Muharani Astuti; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2023)
This study discusses the effect of the disclosure of Islamic ethical values on the financial performance of Islamic banks registered with the Financial Services Authority (OJK) during the 2016-2020 period. The ethical values in this study are the zakat disclosure index (ZDI) and the charity disclosure index (CDI). By using purposive sampling technique, the samples used in this study were obtained from 13 Islamic Commercial Banks in Indonesia. The data in this study were obtained from the bank's annual report in 2016-2020 and analyzed using multiple linear regression. The results of this study indicate that the zakat disclosure index (ZDI) has a positive and significant effect on bank performance. While the Charity Disclosure Index (CDI) does not have a significant effect on bank performance. This study is a more consistent literature survey on the effect of disclosing Islamic ethical values on bank performance and conducting a robustness check to support the findings of the study.